A Multidisciplinary Exploration into Flow in Writing - Rossen-Knill, Deborah F.; Schaefer, Katherine L.; Bayne, Matthew W.; Gegg-Harrison, Whitney; Crasta, Dev; DiMauro, Alessandra (Routledge Research in Writing Studies, 2024)
Offering a multidisciplinary exploration of “flow” and the often-nebulous ways it is conceptualized and operationalized in writing pedagogy, this book addresses a critical gap in writing studies. Bringing together practice-based and scholarly perceptions, it outlines the key features and definitions of flow, and identifies pedagogical approaches and opportunities for classroom instruction. Incorporating perspectives from disciplines including classical rhetoric, composition studies, cognitive science, and linguistics, this book provides a diverse overview of the literature on flow in writing pedagogy. It includes two instructional voice-based and rhetorical grammar-based activities that outline how to recognize and improve flow in writing. In doing so, the book also provides clear examples of how to create an inclusive writing pedagogy that incorporates sensory and analytical perspectives to help readers and writers experience flow and meet their writing goals. As an exploration of flow instruction as it currently stands and might stand in the future, this book will be of interest to students and instructors in the field of academic, professional and creative writing studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.